E Ермағамбетова Ж., Ыдырыс Ә., Аблайханова Н.Т., Бейсенбай A., Жәлел Ж., Б.А. Үсіпбек Экзогенді факторлардың егеуқұйрықтар эритроциттерінің резистенттілігіне әсері: 1Кaзaхский нaционaльный университет имени aль-Фaрaби, г. Алмaты, Кaзaхстaн 2Синьцзянский медицинский университет, г. Урумчи, Китай *E-mail: Raygul.Nyiyazova@kaznu.kz (ҚазҰУ хабаршысы. Экология сериясы, 2017)
he paper examined the therapeutic effect of the enterosorbent under the influence of exogenousfactors and the poisoning of crude oil. We studied the changes in blood biochemical parameters in ratsunder the influence of external factors and the poisoning of crude oil. The use of sorbents can contributeto the protection of public health, which has been exposed to low doses of radiation. At the present timethe role of the use of enterosorbents in medicine is growing. The objects of the study were 8 monthlywhite laboratory male rats weighing 150-200 g. The study was conducted using the analyzer «Bio-Lachema-Test» SA, (HTI, USA) and used immunoradiometric method. As a result of the impact of exogenousfactors and crude oil on rat poisoning when they found changes in blood biochemical parameters andtheir deviation from the performance monitoring, which persisted 30 days after exposure. Because of theeffect of oil, changes were observe in both the liver and the kidneys. The action of crude oil and the useof exogenous factors nanoenterosorbent «Ingo-2» restores the function of the liver, through a protectivemechanism, which includes a hypo and Dysproteinemia glycolysis and restores the activity of the liver,preventing the development of steatosis.